2020
DOI: 10.6004/jnccn.2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Cervical Cancer, Version 1.2020

Abstract: The NCCN Guidelines for Cervical Cancer provide recommendations for diagnostic workup, staging, and treatment of patients with the disease. These NCCN Guidelines Insights focus on recent updates to the guidelines, including changes to first- and second-line systemic therapy recommendations for patients with recurrent or metastatic disease, and emerging evidence on a new histopathologic classification system for HPV-related endocervical adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
217
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(252 citation statements)
references
References 21 publications
2
217
0
1
Order By: Relevance
“…There is also a lack of consensus in the use of RT which is reflected in the NCCN guidelines with lists VBT and/or EBRT as an option for those with grade 1–2 tumors and EBRT with/without VBT with/without systemic therapy [ 26 ]. Furthermore, the NCCN guidelines also state that surveillance may be appropriate for patients undergoing radical hysterectomy with negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of consensus in the use of RT which is reflected in the NCCN guidelines with lists VBT and/or EBRT as an option for those with grade 1–2 tumors and EBRT with/without VBT with/without systemic therapy [ 26 ]. Furthermore, the NCCN guidelines also state that surveillance may be appropriate for patients undergoing radical hysterectomy with negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines from the NCCN (version 1.2020) recommend radiation therapy forms the basis of treatment of patients with CC. 25 Radioresistance is one of the most important reasons for the failure or ineffectiveness of CC radiation therapy. 26,27 Previous studies have found that the abnormal expression of LncRNAs has an important effect on the radioresistance of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for locally advanced carcinoma cervix (LACC) as per National Comprehensive Cancer Network (NCCN) guidelines is concurrent chemoradiation therapy, which further depends on the status of par-aortic lymph nodes involvement [13]. For patients without adenopathy, the standard treatment is radiation therapy (RT) with concurrent platinum-containing chemotherapy along with brachytherapy.…”
Section: Standard Treatment For Locally Advanced Carcinoma Cervix (Stmentioning
confidence: 99%
“…For patients without adenopathy, the standard treatment is radiation therapy (RT) with concurrent platinum-containing chemotherapy along with brachytherapy. The patients with para-aortic lymphadenopathy, the RT is provided to the involved nodes [13].…”
Section: Standard Treatment For Locally Advanced Carcinoma Cervix (Stmentioning
confidence: 99%
See 1 more Smart Citation